The development and psychometric properties of a scalable digital measure of social and emotional wellbeing for middle childhood - Freiberg, Kate (Applied developmental science, 2023)
The need for a new measure of social-emotional wellbeing for children 6–12 years emerged in our collaboration with schools and community agencies in a disadvantaged region of Brisbane, Australia. Our search for an age-appropriate medium led us to develop Clowning Around, a computer game generating data which was assessed for validity and reliability in Study 1 (N = 3,461), revealing four wellbeing factors with satisfactory properties. The imperative to support autonomous use at scale led to development of the Rumble’s Quest user management system and game app, incorporating a slightly modified version of the measure. Reassessment of the factor structure (Study 2: N = 4,333) supported Study 1 results but extended factors to five: School Attachment, Social Wellbeing, Emotional Wellbeing, Family Support, and Behavioral Conformity. The measure exhibits sound convergent and concurrent validity and is a reliable and practical tool for data-guided service planning and evaluation, and for monitoring child wellbeing trends.